2020
DOI: 10.3390/diagnostics10110917
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Serum Ferritin in Combination with Alanine Aminotransferase and Glucose Levels for Noninvasive Assessment of NAFLD: Fatty Liver in Obesity (FLiO) Study

Abstract: The identification of affordable noninvasive biomarkers for the diagnosis and characterization of nonalcoholic fatty liver disease (NAFLD) is a major challenge for the research community. This study aimed to explore the usefulness of ferritin as a proxy biomarker of NAFLD condition, alone or in combination with other routine biochemical parameters. Subjects with overweight/obesity and ultrasound-confirmed liver steatosis (n = 112) from the Fatty Liver in Obesity (FLiO) study were assessed. The hepatic evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…TG and HDL have been proved to be closely related to fatty liver (49), and the result of multivariate analysis also re ected the signi cant in uence of TG and HDL in the identi cation of patients with MAFLD. Consistent with our study, existed evidences showed that elevated ALT played an important role in the occurrence and progression of FLD (50,51). Our nding also suggested that ALT abnormalities should be considered as an important factor in the classi cation of high-risk individuals for MAFLD.…”
Section: Discussionsupporting
confidence: 91%
“…TG and HDL have been proved to be closely related to fatty liver (49), and the result of multivariate analysis also re ected the signi cant in uence of TG and HDL in the identi cation of patients with MAFLD. Consistent with our study, existed evidences showed that elevated ALT played an important role in the occurrence and progression of FLD (50,51). Our nding also suggested that ALT abnormalities should be considered as an important factor in the classi cation of high-risk individuals for MAFLD.…”
Section: Discussionsupporting
confidence: 91%
“…Several cross-sectional and case-control studies have assessed the association between serum ferritin levels and the risk of NAFLD [24][25][26][27]. Recent a cross-sectional study found that serum ferritin positively associated with alanine aminotransferase (ALT) among subjects with overweight/obesity and ultrasound-con rmed liver steatosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional and case-control studies have assessed the association between serum ferritin levels and the risk of NAFLD [24][25][26][27]. Recent a cross-sectional study found that serum ferritin positively associated with alanine aminotransferase (ALT) among subjects with overweight/obesity and ultrasound-con rmed liver steatosis [24]. Two cross-sectional studies also showed that higher serum ferritin was associated with a higher risk of NAFLD and elevated ALT among Chinese adults with normal weight [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, participants were merged and compared together. The habitual dietary intake was registered with a validated semi-quantitative food frequency questionnaire (FFQ) of 137 items, both at baseline and after the 6-month intervention [38,39]. The composition of the food items was derived from accepted Spanish food composition tables as previously described [4,40].…”
Section: Dietary and Lifestyle Interventionmentioning
confidence: 99%